Ballenesque : Roger Ballen : a retrospective - Ballen, Roger (Thames & Hudson, 2017)
Roger Ballen is best known for his psychologically powerful and intricately layered images that exist in a space between painting, drawing, installation, and photography. Ballenesque is the first comprehensive retrospective of his work. Separated into four parts, Ballenesque takes readers on a chronological journey through Ballen's entire oeuvre, including both iconic images and previously unpublished works. Part I explores Ballen's formative artistic influences and his later rediscovery of boyhood through photography, culminating in his first published monograph, Boyhood, in 1979. Part II charts the period between 1980 and 2000, during which time he released his seminal monograph Outland. Part III covers the years 2000-2013, when Ballen achieved global recognition and his work began to veer away from portraiture altogether. Finally, in Part IV, Ballen reflects on his career.